2021
DOI: 10.1002/ppul.25241
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory morbidity associated with viral respiratory infections during neonatal stage in premature infants

Abstract: Background and Objective Very low birth weight (VLBW) infants are highly susceptible to viral respiratory infections (VRIs), even during admission to the neonatal intensive care unit (NICU). Although the role of VRI in childhood in the development of recurrent wheezing and long‐term asthma is well known, information on the impact in later morbidity of VRI in the neonatal period is lacking. We aimed to explore the occurrence of recurrent wheezing over the first 2 years of life according to VRI status during NIC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Our research suggests that premature infants with symptomatic VRIs during NICU admission have an increased risk of developing recurrent wheezing during the first two years of age. There is an increasing amount evidence to suggest that early life VRIs favour the development of an abnormal respiratory epithelial layer, leading to deviations in T cell maturation along the pro-allergic T2 pathway [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our research suggests that premature infants with symptomatic VRIs during NICU admission have an increased risk of developing recurrent wheezing during the first two years of age. There is an increasing amount evidence to suggest that early life VRIs favour the development of an abnormal respiratory epithelial layer, leading to deviations in T cell maturation along the pro-allergic T2 pathway [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…This patient was treated with invasive mechanical ventilation, solumedrol, and hydroxychloroquine in the PICU and discharged home on room air after a 27 day hospital stay. 27 Although the reported incidences of RVIs of any type in the NICU are relatively low, 8,28,29 preterm infants with established BPD are highly susceptible to in-hospital RVIs due to their immature immune system 30 and need for prolonged initial NICU hospitalization. 31 Given the underlying pulmonary insufficiency that characterizes lung function in infants with established BPD, 32,33 exposure to RVIs can cause major short-and long-term respiratory morbidities.…”
Section: Discussionmentioning
confidence: 99%
“…This is of particular importance for high‐risk preterm infants, given the relatively high occurrence of rhino/enterovirus RVIs in this population, which are associated with increased need for respiratory support, nursing care, and medical resources 3,8,18,19 . A recent report by Sánchez García et al 29 suggested that any symptomatic RVI in the NICU was associated with a significantly increased odds of respiratory morbidity in early childhood. Following discharge from the NICU, multiple studies have identified the increased susceptibility of BPD patients to adverse respiratory outcomes following RVIs in early childhood, particularly with respiratory syncytial virus (RSV) infection 4,34–36 .…”
Section: Discussionmentioning
confidence: 99%
“…Various surveillance studies have shown that RVIs, including those caused by respiratory syncytial virus (RSV), human rhinovirus (hRV), adenovirus (hAdV), metapneumovirus (hMPV), bocavirus (hBoV), or human coronavirus (hCoV), are very frequent in Neonatal Intensive Care Units (NICUs) 2-4 . Despite causing subtle or even asymptomatic infections, RVIs may have an important mid and long-term impact on children's health 4,5 .In preterm infants, immune response to RVIs and their pathophysiology are poorly understood 6 . Severe RVIs occurring in infancy have been found to be an independent risk factor for the subsequent development of asthma and recurrent wheezing 7,8 .…”
mentioning
confidence: 99%
“…Various surveillance studies have shown that RVIs, including those caused by respiratory syncytial virus (RSV), human rhinovirus (hRV), adenovirus (hAdV), metapneumovirus (hMPV), bocavirus (hBoV), or human coronavirus (hCoV), are very frequent in Neonatal Intensive Care Units (NICUs) 2-4 . Despite causing subtle or even asymptomatic infections, RVIs may have an important mid and long-term impact on children's health 4,5 .…”
mentioning
confidence: 99%